Liver chemistry in new-onset Henoch-Schönlein syndrome - Giulia Rosti; Gregorio P. Milani; Emanuela A. Laicini; Emilio F. Fossali; Mario G. Bianchetti (BMC, 2017)
Abstract Background Henoch-Schönlein syndrome is a systemic small-vessel leukocytoclastic vasculitis that usually present with cutaneous, gastrointestinal, articular and renal manifestations. Little is known on liver involvement in this syndrome. This study investigated liver chemistry and creatine kinase in Henoch-Schönlein children. Case presentation Alanine aminotransferase, aspartate aminotransferase, γ-glutamyltransferase, lactate dehydrogenase, total bilirubin, prothrombin time and creatine kinase were assessed in 75 consecutive pediatric patients (41 boys and 34 girls aged from 2.9 to 17 years) with new-onset Henoch-Schönlein syndrome. Mildly altered values were found in 7 (9%) patients (5 boys and 2 girls aged from 3.3 to 17 years). In the mentioned cases, all tests returned to normal at a 2-4-week follow-up. Conclusions This preliminary study points out that altered and self-remitting liver parameters occur in approximately 10% of children with Henoch-Schönlein syndrome.